Sound classification using deep learning for hard of hearing and deaf people - Habib, Md.Adnan; Arefeen, Zarif Raiyan; Hussain, Arafat; Shahriyer, S.M.Rownak; Islam, Tanzid (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.